Anti‐citrullinated‐protein‐antibody‐specific intravenous immunoglobulin attenuates collagen‐induced arthritis in mice. (24th September 2015) - Svetlicky, N.; Kivity, S.; Odeh, Q.; Shovman, O.; Gertel, S.; Amital, H.; Gendelman, O.; Volkov, A.; Barshack, I.; Bar‐Meir, E.; Blank, M.; Shoenfeld, Y.
Summary: Administration of intravenous immunoglobulin (IVIg) is a recognized safe and efficient immunomodulation therapy for many autoimmune diseases. Anti‐idiotypic antibody binding to pathogenic autoantibodies was proposed as one of the mechanisms attributed to the protective activity of IVIg in autoimmunity. The aim of this study was to fractionate the anti‐anti‐citrullinated protein anti‐idiotypic‐antibodies (anti‐ACPA) from an IVIg preparation and to test it as a treatment for collagen‐induced arthritis in mice. IVIg was loaded onto an ACPA column. The eluted fraction was defined as ACPA‐specific‐IVIg (ACPA‐sIVIg). Collagen‐induced‐arthritis (CIA) was induced in mice. Mice were treated weekly with ACPA‐sIVIg, low‐dose‐IVIg, high‐dose‐IVIg and phosphate‐buffered saline (PBS). Sera‐ACPA titres, anti‐collagen anitbodies and cytokine levels were analysed by enzyme‐linked immunosorbent assay (ELISA); antibody‐forming‐cell activity by enzyme‐linked imunospot (ELISPOT) assay; and expansion of regulatory T cell (Treg ) population by fluorescence activated cell sorter (FACS). ACPA‐sIVIg inhibited ACPA binding to citrullinated‐peptides (CCP) in vitro 100 times more efficiently than the IVIg compound. ACPA‐sIVIg was significantly more effective than the IVIg‐preparation in attenuating the development of collagen‐induced arthritis. Splenocytes from CIA mice treated with ACPA‐sIVIg reduced the ACPA and anti‐collagen‐antibody titres, including the number of anti‐collagen and ACPA antibody‐forming cells. In parallel, splenocytes from ACPA‐sIVIg treated mice secreted higher levels of anti‐inflammatory cytokines and lower proinflammatory cytokines. The ACPA‐sIVIg inhibitory potential was accompanied with expansion of the Treg population. Low‐dose IVIg did not affect the humoral and cellular response in the CIA mice in comparison to the PBS‐treated mice. Based on our results, IVIg may be considered as a safe compound for treating patients with rheumatoid arthritis by neutralizing pathogenic autoantibodies, reducing proinflammatory cytokines and expanding the Treg population.